2010
DOI: 10.1111/j.1600-0854.2010.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Facets of Ubiquitination in the Regulation of Notch Signaling Pathway

Abstract: The Notch signaling pathway regulates numerous aspects of metazoan development and tissue renewal. Deregulation or loss of Notch signaling is associated with a wide range of human disorders from developmental syndromes to cancer. Notch receptors and their ligands are widely expressed throughout development, yet Notch activation is robustly controlled in a spatio-temporal manner. Within the past decades, genetic screens and biochemical approaches led to the identification of more than 10 E3 ubiquitin ligases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 88 publications
0
68
0
Order By: Relevance
“…The role of ubiquitin in endocytosis remains unclear: on the one hand, cargo-specific ubiquitination may be required to enable binding to the UBD of an adaptor; on the other hand, monoubiquitination of the adaptor (Eps15, Epsin) may be inhibitory because of its closed conformation. Because CHIP ubiquitinates Epsin, it is probably a negative factor in the endocytosis of cargo that needs Epsin for endocytosis such as in the case of Notch and the EGF receptor (45)(46)(47). In this study, CHIP is clearly acting as a positive factor for GHR endocytosis.…”
Section: Discussionmentioning
confidence: 77%
“…The role of ubiquitin in endocytosis remains unclear: on the one hand, cargo-specific ubiquitination may be required to enable binding to the UBD of an adaptor; on the other hand, monoubiquitination of the adaptor (Eps15, Epsin) may be inhibitory because of its closed conformation. Because CHIP ubiquitinates Epsin, it is probably a negative factor in the endocytosis of cargo that needs Epsin for endocytosis such as in the case of Notch and the EGF receptor (45)(46)(47). In this study, CHIP is clearly acting as a positive factor for GHR endocytosis.…”
Section: Discussionmentioning
confidence: 77%
“…A primary effect of Gleevec treatment is the inhibition of GSK3b phosphorylation, unphosphorylated GSK3b is activated, and phosphorylates Int3 marking it for ubiquitination. The Notch-ICD is ubiquitinated by E3 ubiquitin ligases, 28 such as Fbw7 (also known as Cdc4 and Sel10), that can ubiquitinate Notch-ICD within its PEST domain, leading to its proteasomal degradation. [30][31][32]39 It has also been shown that the interaction between Sel-10 and Notch proteins is phosphorylation dependent, 32 suggesting that Notch-ICD phosphorylation precedes its ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Notch receptors and their ligands are potential substrates for ubiquitin addition by E3 ligases. [27][28][29] It has been demonstrated that Notch-ICD is rapidly polyubiquitinated and degraded through the proteasomal pathway, and the E3 ubiquitin ligase accounting for these modifications is Fbw7/Sel-10. [30][31][32] To elucidate the mechanism by which Gleevec inhibits Notch signaling, we established in vitro and in vivo systems using cell lines and transgenic mice.…”
Section: 2mentioning
confidence: 99%
“…These results, together with the observation that presenilin works optimally in an acidic environment such as that present in the endosome/lysosome [283], support the idea that endosomal sorting of Notch is required for best activation of its S3 cleavage. However, unrestricted access of Notch receptors to the endosome should be prevented, since the acidic pH could dissociate the NECD, thus triggering ligand-independent Notch activation [210].…”
Section: Notch Receptor Trafficking and Endosomal-emanating Signalsmentioning
confidence: 99%
“…Genetic evidence in invertebrates and mammals points to ubiquitylation (also referred to as ubiquitination) as the master regulatory mechanism controlling the endocytosis implicated in Notch signaling activation (reviewed in [209][210][211]). Ubiquitylation, i.e.…”
Section: Specialized Endocytic Machinerymentioning
confidence: 99%